Are Spanish companies involved in profit shifting? Consequences in terms of tax revenues - Ángela Castillo Murciego; Julio López Laborda (Kiel Institute for the World Economy (IfW), 2016)
In this paper the authors analyze the existence of profit shifting by companies located in Spain. Using a sample of 1,380 Spanish subsidiaries owned by foreign OECD and EU parent companies from the AMADEUS Database for the period 2005-2014 and a simple tax rate difference as a measure of the profit shifting tax incentive, the authors obtain a negative effect of corporate income taxes on reported profits, which is consistent with the profit shifting activity of corporations and matches the empirical results in the literature. Furthermore, they derive a negative effect from this profit shifting activity in terms of tax revenues for Spain.
Keywords: F23; F69; H25; H26; H32; 330; profit shifting; multinational corporations; tax revenues; Spain